Direct Interaction between N-Acetylcysteine and Cytotoxic Electrophile-An Overlooked In Vitro Mechanism of Protection - Mlejnek, Petr (Antioxidants (Basel, Switzerland), 2022)
In laboratory experiments, many electrophilic cytotoxic agents induce cell death accompanied by reactive oxygen species (ROS) production and/or by glutathione (GSH) depletion. Not surprisingly, millimolar concentrations of N-acetylcysteine (NAC), which is used as a universal ROS scavenger and precursor of GSH biosynthesis, inhibit ROS production, restore GSH levels, and prevent cell death. The protective effect of NAC is generally used as corroborative evidence that cell death induced by a studied cytotoxic agent is mediated by an oxidative stress-related mechanism. However, any simple interpretation of the results of the protective effects of NAC may be misleading because it is unable to interact with superoxide (O2•-), the most important biologically relevant ROS, and is a very weak scavenger of H2O2. In addition, NAC is used in concentrations that are unnecessarily high to stimulate GSH synthesis. Unfortunately, the possibility that NAC as a nucleophile can directly interact with cytotoxic electrophiles to form non-cytotoxic NAC-electrophile adduct is rarely considered, although it is a well-known protective mechanism that is much more common than expected. Overall, apropos the possible mechanism of the cytoprotective effect of NAC in vitro, it is appropriate to investigate whether there is a direct interaction between NAC and the cytotoxic electrophile to form a non-cytotoxic NAC-electrophilic adduct(s).
Keywords: N-acetylcysteine; electrophile; N-acetylcysteine-electrophile adduct; mechanism of protection; nucleophile